Time resolved study of laser diode characteristics during pulsed operation - Eichler, Christoph; Schad, Sven-Silvius; Seyboth, Matthias; Habel, Frank; Scherer, Marcus; Miller, Stephan; Weimar, Andreas; Lell, Alfred; Härle, Volker; Hofstetter, Daniel (My University, 2003)
Under pulsed operation, time dependent spectral and electro-optical measurements on GaN-based laser diodes show a considerable red shift in the emission wavelength and a decreasing voltage drop across the device. These changes appear on a rather short time scale in the microsecond range. During a 3.7 microsecond long pulse, a temperature increase of approximately 50 K is obtained using different experimental methods. This value agrees well with numerical simulations based on the thermal properties of the material.